2019
DOI: 10.3390/ani10010027
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Housing Conditions on Reliability of Immunocastration and Consequences for Growth Performance of Male Pigs

Abstract: Simple Summary: Surgical castration of male piglets is societally criticized as it is painful and violates the integrity of the animals. Pork production with boars and immunocastrates are possible alternatives. Even if immunocastration is an animal-welfare-friendly alternative, its market share is low and the reliability of this technique is discussed controversially within the pork chain. Currently, the number and the reason for non-responders to vaccination are not clear. Various factors may contribute to im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 49 publications
2
43
1
Order By: Relevance
“…These studies, however, refer to standardized trials with fixed ages at slaughter. It is well known that the growth performance of immunocastrates increases significantly after the second vaccination [ 19 , 30 , 31 ], as immunocastrates consume significantly more feed after the second vaccination [ 32 ]. For this reason, the timing of the second vaccination has a decisive impact on growth performance and thus indirectly on the final hot carcass weight of immunocastrates with a fixed fattening period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies, however, refer to standardized trials with fixed ages at slaughter. It is well known that the growth performance of immunocastrates increases significantly after the second vaccination [ 19 , 30 , 31 ], as immunocastrates consume significantly more feed after the second vaccination [ 32 ]. For this reason, the timing of the second vaccination has a decisive impact on growth performance and thus indirectly on the final hot carcass weight of immunocastrates with a fixed fattening period.…”
Section: Discussionmentioning
confidence: 99%
“…As described in the review by Olsson and Pickova [ 44 ], it is well known that management (housing conditions, age, genetics, sex and feeding) can influence various pork quality parameters such as water holding capacity, fat content, tenderness, color and aroma. We also know that stress and intensive housing conditions can have a negative impact on growth performance and hot carcass weight in pigs [ 31 , 45 ]. An experiment with organic housing conditions and organic feed showed that the feed had no influence on the lean meat content of pig carcasses, but the housing conditions did.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hams for this study originate from a wider study evaluating immunocastration (for more details see [12]). We compared hams from surgical castrates (SC), immunocastrates (IC) and entire males (EM) of one crossbreed (Pietrain x German Landrace), which were fattened with the same diet ad libitum.…”
Section: Origin and Processing Of Hamsmentioning
confidence: 99%
“…An objection to the use of intact males would be the increased stress due of aggressive and mounting behavior during the finishing period [187]. Contrastingly, good results can be obtained by employing immuno-castration with pigs managed in different housing systems [188]. However, economical comparisons conducted in Germany showed that barrows performed better than boars and immunocastrates [189].…”
Section: Painful Interventionsmentioning
confidence: 99%